Teaching physical education for learning - Rink, Judith E. (New York McGraw Hill, 2020)
Teaching physical education for learning, eighth edition focuses on the instructional skills teachers need to be effective in producing student learning. This text provides students who are working to become physical education teachers with the understanding that learning to be a teacher begins with understanding teaching as a process of selecting goals and designing educational experiences consistent with how students learn to help students achieve those goals. Focusing on physical education from kindergarten through grade 12, this user-friendly text emphasizes teaching strategies and theories to give future teachers a foundation for designing effective learning experiences
1. teaching physical education: an orientation -- 2. Factors that influence learning -- 3. Designing learning experiences and instructional tasks -- 4. Task presentation -- 5. Content analysis and development -- 6. Developing and maintaining a learning environment -- 7. Teaching during activity -- 8. Teaching strategies -- 9. Student motivation, personal growth, and inclusion -- 10. Planning -- 11. Assessment in the instructional process -- 12. Content-specific pedagogy -- 13. The teacher as continuous learner -- 14. Observing teacher and student behavior
"This international student edition is for use outside of the U.S." - Book cover
Keywords: Physical education and training -- Study and teaching; Physical education for children -- Study and teaching